KEUNGGULAN KOMPETITIF YANG DALAM MENCIPTAKAN INOVASI UNTUK KEWIRAUSAHAAN STRATEGIS - Bilgies, Ana Fitriyatul (IAIN Tulungagung, 2017)
At the moment in the environment of competitive advantage use for companyneeds to be very agile and adaptive. While often unable to make a certainlevel of performance based on technology on existing progress, the company isalso came often to login of in the new technology emerging. How to addressentrepreneurship strategically as a way which the company simultaneouslyexploit competitive advantage they are now while explore for opportunitiesfor the future . On this Reaching based on balance between exploration andexploitation of consists of more than just allocated of resources in comparable between the two the process. And so as be discussed, For the exploration to the exploitation of is process that it should be, structure and culturally distinct.